(untitled) (Ideal Journal of Multidisciplinary Research, 2026)
This article provides an in-depth analysis of the pedagogical and psychological characteristics of developing riskological competence in future teachers. The increasing complexity of the educational process, the emergence of new threats in the digital environment, and the need for rapid and responsible decision-making in professional activities require future educators to acquire skills in recognizing, assessing, and managing risks. Therefore, the development of riskological competence is examined as an essential component of modern teacher training.